The Possible Clinical Predictors of Fatigue in Parkinson’s Disease: A Study of 135 Patients as Part of International Nonmotor Scale Validation Project - Vinod Metta; Kartik Logishetty; P. Martinez-Martin; Heather M. Gage; P. E. S. Schartau; T. K. Kaluarachchi; Anne Martin; Per Odin; P. Barone; Fabrizio Stocchi; A. Antonini; K. Ray Chaudhuri (Parkinson's Disease)
Fatigue is a common yet poorly understood and underresearched nonmotor symptom in Parkinson’s disease. Although fatigue is recognized to significantly affect health-related quality of life, it remains underrecognised and empirically treated. In this paper, the prevalence of fatigue as measured by a validated visual analogue scale and the Parkinson’s disease nonmotor symptoms scale (PDNMSS) was correlated with other motor and nonmotor comorbidities. In a cohort of patients from a range of disease stages, occurrence of fatigue correlated closely with more advanced Parkinson’s disease, as well as with depression, anxiety, and sleep disorders, hinting at a common underlying basis.